SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA PPA DAN BBM DENGAN METODE SAW BERBASIS WEB - Malelak, Yohanis (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2021)
Educational institutions, especially universities, a lot of scholarships are offered to students. Scholarships are also given to students at STIKOM UYELINDO in the form of PPA and BBM scholarships. Some problems that often occur such as inaccurate selection process because of the large number of scholarship applicants that must be adjusted to the existing criteria, then in determining the right students do not even get a scholarship and students who are not entitled to get a scholarship instead get a scholarship and the selection process is still manual because Student data will be compared one by one to the scholarship criteria so that the selection process requires accuracy and time so this is not efficient. The decision support system application is a way to deal with the problem of determining scholarship recipients. This application uses Fuzzy Multiple Attribute Decision Making (FMADM) with the Simple Additive Weighting (SAW) method. The SAW method was chosen because this method determines the weight of each predetermined criterion then continues in the normalization process in accordance with the equation in the SAW method and then continues with the ranking process to select the best alternative, in this case what is meant is students who are entitled to receive scholarships. The results of this study are in the form of an application decision support system for the selection of scholarship recipients using the web-based simple additive weighting method. Based on research results from the application of decision support systems for acceptance of ppa and fuel scholarships using the web-based saw method) this makes it easy for the student affairs bureau selection section to determine scholarship recipients according to existing criteria, faster and on target as expected.